Adapting Legal Culture: Legislation and Interpretation in Tax Law (European Journal of Marketing and Economics, 2023)
Legal culture is defined as a way of describing relatively stable patterns of legally oriented social behaviour and attitudes. Adapting legal culture is possible, while the adapted legislation makes a shift in the social reality, especially in transition to democracy. As social behaviour depends on other elements, such as historical and cultural backgrounds of a society, the reaction for the legal adaption may differ from one country to another. So, the legislation in two countries may be the same; but the interpretation and the implementation of the law may be different.  As tax norms also have an economic aspect, factors effecting the results of the tax law adaption may be historical, cultural and also economic. Adapting legal culture is more comprehensive than transplanting legal mechanisms and importing other legal systems, it is not only translating legislation but also creating a differential fitness; a different aspect of rights and principles of law design. As tax law includes social norms as well as financial norms and is a multidisciplinary branch of law, the adaption of tax law needs justification of perceived fairness and common understanding of basic law principles and rights. If the perception of law is different, the interpretation of law may create a sui generis version of the adapted law. In this article, the question to be answered is how the historical, cultural and economic factors differ adapted tax systems in practice by the interpretation of law.
Keywords: Adapting Legal Culture Legislation and Interpretation in Tax Law